Studi Kelayakan Bisnis melalui Analisis Aspek Pemasaran dan Aspek Manajemen Pada UMKM Nasi Uduk di Kabupaten Bekasi (Studi Kasus Pada Nasi Uduk Bu Asiah Rawa Sentul) - Metia Septiani; Rizka Fitri Ramadanty; Dwi Astuti (CV. ITTC INDONESIA, 2025)
Nasi Uduk is one of the culinary delights that is popular with local people. In developing a business, it is necessary to carry out a business feasibility study analysis so that the business being run is worthy of development. This research aims to analyze the feasibility of the Nasi Uduk Bu Asiah business in Rawa Sentul, Kab. Bekasi. This research focuses on marketing aspects and management aspects. This study uses a qualitative approach through direct observation and interviews with business owners. The results of this research indicate that Nasi Uduk Bu Asiah has good business potential by utilizing offline (word of mouth) and online marketing strategies via social media. A strategic business location and a combination of quality products at affordable prices are key factors for success.